2011
DOI: 10.4236/jep.2011.28129
|View full text |Cite
|
Sign up to set email alerts
|

Surveying of Pesticides Commonly on the Markets of Iran in 2009

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…Pesticides are chemical or biological substances used to control pests ( 50 ), including organophosphate, carbamate, and phosphide compounds ( 51 ). Application of pesticides in Iran has been increasing since 2000 ( 52 ).…”
Section: Resultsmentioning
confidence: 99%
“…Pesticides are chemical or biological substances used to control pests ( 50 ), including organophosphate, carbamate, and phosphide compounds ( 51 ). Application of pesticides in Iran has been increasing since 2000 ( 52 ).…”
Section: Resultsmentioning
confidence: 99%
“…Dehghani et al [ 20 ] conducted the research on pesticides consumed in the Iran market on 2009 and the results showed that "60 types of pesticides were used in Iran. Moreover, they suggested that the responsible authorities should provide the necessary information on the permissible use amounts of pesticides, their protection strategies and the hazards of pesticides on users".…”
Section: Discussionmentioning
confidence: 99%
“…Organophosphate poisoning is one of the main clinical problems in the world, especially in developing countries, where is associated with high mortality [ 5 ] [ 8 ] [ 9 ]. About 28.4% of the agricultural pesticides used in Iran are organophosphorus [ 10 ]. Insecticides are organophosphorus compounds that lead to toxicity in humans by inhibiting the acetylcholinesterase enzyme [ 11 ].…”
Section: Introductionmentioning
confidence: 99%